The Effect of Service Quality and Digital Marketing on Consumer Loyalty through Consumer Satisfaction as a Mediation Variable at PT Pos Indonesia, Yogyakarta City - Kusuma, Chusnu Syarifa Diah; Hariansyah, Mochammad Aditya; Putra, Ijai Pratama (International Journal of Social Science and Business, 2025)
This study aims to evaluate the impact of service quality and digital marketing on consumer loyalty at PT Pos Indonesia, Yogyakarta, with a focus on understanding how customer satisfaction mediates these relationships. The context of this research is particularly relevant in light of the company’s recent decline in market share and its attempts to adapt to a rapidly changing competitive environment in the expedition industry.  A quantitative approach with a causal design was employed. Data were collected through an online questionnaire from 155 respondents who had used PT Pos Indonesia's services. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was used to test the hypotheses and analyze the relationships between service quality, digital marketing, customer satisfaction, and consumer loyalty. The analysis revealed that service quality has a significant positive effect on both customer satisfaction and loyalty. Customer satisfaction was found to mediate the relationship between service quality and loyalty. In contrast, digital marketing showed a negative but near-significant effect on consumer loyalty and had no significant impact on customer satisfaction. The mediating effect of customer satisfaction on the relationship between digital marketing and loyalty was not significant.  This study highlights the critical role of service quality in enhancing customer loyalty, both directly and indirectly through customer satisfaction. Companies, particularly PT Pos Indonesia, should focus on improving service quality as it significantly influences consumer loyalty. Digital marketing strategies, however, need reevaluation, as they do not seem to align with customer expectations and have not proven effective in fostering loyalty. The study’s findings suggest that companies should prioritize service quality improvements and adopt a more targeted, customer-oriented digital marketing approach. Future research could expand on these findings by exploring the impact of external factors or conducting comparative analyses with competitors in the expedition industry.